Omissão do cuidado de enfermagem em um hospital de ensino - Lima, Juliana Carvalho de (2018)
INTRODUCTION: Given the complexity of work environments in healthcare facilities, the multiplicity of activities required in the provision of care to hospitalized persons and the shortage of resources, the nursing team may feel unable to deliver the care required by patients in some situations, and may shorten, delay or even omit it. Nursing care omission is a universal problem, with potential negative consequences to patients, professionals, and facilities. OBJECTIVES: To analyze the omission of nursing care in the assistance to hospitalized patients. METHOD: This analytical crosssectional study was developed in a teaching hospital in the state of Goiás. Data were collected from April to December 2017, by means of the instrument MISSCARE - BRASIL. The study participants were nurses, and nursing technicians and aides who worked in 10 hospitalization units. Descriptive analyses of simple frequency, central tendency and dispersion were conducted. The differences in the prevalence of nursing care omission by professional category were calculated using Pearson‟s chi square test or Fisher‟s exact test. Associated factors were verified by means of bivariate and multivariate analyses. The study was approved by the institution‟s ethics committee, under protocol no. 1.922.667, CAAE: 62612216.0.0000.5078. RESULTS: A total of 267 nursing professionals participated in the study, with a mean age of 43 years, of whom 66.3% were nursing technicians. Omission of nursing care elements was identified, and the most prevalent were: sitting the patient out of the bed (70.3%), walking three times a day (69.1%) and participating in discussions with the interdisciplinary team about patient care (67.2%). Four nursing care elements were more reported by the nurses as omitted (p< 0.05): changing the patient‟s position every two hours, full record on the patient‟s chart, infusion and venous access care and answering to a patient‟s call within 5 minutes. Already the wound/skin lesion care obtained greater omission by the technicians and auxiliary of nursing. The most prevalent reasons for omitting care were: insufficient number of personnel (85.4%), insufficient number of personnel for care or administrative tasks (81.6%) and unexpected increase in the quantity and/or severity of patients in the unit (79.8%). The highest occurrence of nursing care omission was associated with the medical clinic and surgery hospitalization units (p<0.05). The professionals who reported satisfaction with the job and with teamwork had fewer rates of care omission when compared with those who reported dissatisfaction (p< 0.05). Higher rates of care omission were associated with absence to work in the previous three months (p< 0.05). CONCLUSION: The study evidenced that nursing care has been omitted, especially due to systemic flaws, which must be eliminated to favor patient safety. Studies like this confirm that nursing has been performed in unfavorable situations to the comprehensive fulfillment of the care process, demanding efforts to plan and adopt strategies to prevent care omission and improve care practice.